Enhancing Historical Narrative through Application of Staging Techniques in 3D Animation “How Islam Spread Around the World” - Fadila, Juniardi Nur; Hassan, Sayyed Aamir; Arkan, Maulana Hilmi; Indaru, Danendra Farrel Bhagawanta; Diano, Senator Marcielio Cheviray (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
This research addresses the challenge of effectively conveying the historical narrative of Islam's spread through 3D animation. The primary objective is to explore the potential of staging techniques in enhancing message delivery and audience engagement. Staging, a method that emphasizes scene element arrangement, character placement, and camera perspective, is pivotal for a clear and impactful narrative. Through this technique, elements are organized to guide viewers' attention and emphasize the intended message. This study demonstrates that careful alignment of characters, backgrounds, and camera angles, combined with visual symbolism representing Islamic values, can significantly enhance the narrative's depth and viewer comprehension. Experiments reveal that strategic staging not only strengthens the storyline but also boosts audience understanding. The research underscores the importance of staging in 3D animation, especially for intricate narratives like the spread of Islam. It offers insights into the advantages of staging over traditional methods, emphasizing its role in narrative comprehension, deeper meaning conveyance, and audience engagement.